Chemical vs. herbal formulations as pre-procedural mouth rinses to combat aerosol production: A randomized controlled study - Koduganti Rekha Rani; Manasa Ambati; Jammula Surya Prasanna; Indumathy Pinnamaneni; Panthula Veerendranath Reddy; Dasari Rajashree (Wolters Kluwer Medknow Publications, 2014)
Background: Disease transmission and barrier techniques are the key concerns during ultrasonic instrumentation as this procedure has the hazard of aerosol production which has a multitude of deleterious effects on the body. The aerosol produced can affect both the patient and the clinician. The aim of this study was to assess the importance of pre-procedural rinsing before scaling by ultrasonic instrumentation and to compare the efficacy of commercially available herbal mouth rinse and a Chlorhexidine gluconate mouth rinse with a control group. The study was conducted from 1 st February to 15 th April 2012 in a tertiary referral care hospital. The study was approved by the institutional ethical committee. This was a randomized single blinded interventional study, where in 36 patients equally divided into three groups participated. Material and Methods: Thirty six patients were recruited in this study aged between 18-35 years. All patients had plaque index scores between1.5-3.0, and were categorized into three groups. Patients with systemic diseases and on antibiotic therapy were excluded. Group A or control group underwent scaling with water as pre-procedural rinse, Group B used 20 ml of 0.2% Chlorhexidine and group C were administered 18 ml of a herbal pre-procedural rinse. Aerosol splatter produced during the procedure were collected on blood agar plates and sent for microbiologic analysis for the assessment of bacterial Colony Forming Units (CFUs). The mean CFUs and standard deviation (SD) for each group were measured. Post hoc test was used to compare the differences between three groups, Control (A) Chlorhexidine (B) and Herbal (C). Results: The mean Colony Forming Units (CFUs) for control group was 114.50, Chlorhexidine group was 56.75 and herbal rinse group was 47.38. Conclusion: Pre-procedural rinsing was found to be effective in reducing aerosol contamination during ultrasonic scaling though no statistically significant difference was found between the two test groups Chlorhexidine and Herbal mouth rinse.